2016
DOI: 10.1007/s11837-016-1967-1
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Approach Towards Computational Characterization of Dislocation Microstructure

Abstract: Dislocations -linear defects within the crystal lattice of, e.g., metals -already have been directly observed and analyzed for nearly a century. While experimental characterization methods can nowadays reconstruct three-dimensional pictures of complex dislocation networks, simulation methods are at the same time more and more able to predict the evolution of such systems in great detail. Concise methods for analyzing and comparing dislocation microstructure, however, are still lagging behind. We introduce a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The D2C framework (Sandfeld and Po, 2015;Steinberger et al, 2016) is based on treating dislocations as directed curves with additional physical properties, i.e., the slip plane normal, and the Burgers vector. Dislocations represent the boundary of an area over which slip displacement between two adjacent lattice planes has occurred.…”
Section: D2c-discrete-to-continuousmentioning
confidence: 99%
See 1 more Smart Citation
“…The D2C framework (Sandfeld and Po, 2015;Steinberger et al, 2016) is based on treating dislocations as directed curves with additional physical properties, i.e., the slip plane normal, and the Burgers vector. Dislocations represent the boundary of an area over which slip displacement between two adjacent lattice planes has occurred.…”
Section: D2c-discrete-to-continuousmentioning
confidence: 99%
“…This makes it problematic to directly operate with these objects. We will therefore take a new approach: Based on the discrete-to-continuous (D2C) framework (Sandfeld and Po, 2015;Steinberger et al, 2016), which "borrows" the field variables of a continuum theory of dislocation dynamics. This method was already successfully used to study the emergent microstructural features of molecular dynamics simulations of plastic deformation via scratching (Gunkelmann et al, 2017) and during shock loading (Kositski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the curvature is independent of the density, such that even averaging voxels with very low density will have a finite curvature value. In Steinberger et al [22] the authors have already shown that this counter-intuitive behavior does not exist if the curvature density, which is a product of density and curvature, is used.…”
Section: A Continuum Field Description Of An MD Simulationmentioning
confidence: 99%
“…To compute the stresses associated with dislocations within a specimen for the characterization of the microstructure [1,2], we start by considering a linear elastic model described by div σ = 0, σ = σ T , σ = C : ε el , and ε el = 1 2 ∇u + (∇u) T to solve for the displacements u. Here, σ is the stress tensor, ε el the elastic strain tensor, and C the stiffness tensor.…”
Section: Mechanical Modelmentioning
confidence: 99%